SALVING DISTRIBUTION INFORMATION SYSTEM ON PT. ANUGERAH ARGON MEDICA - Halimah Yunus (Jurnal Informatika, 2015)
Medica's Argon godsend constitute moving firm at salving sell area filing system and its reporting is still utilize archives and ledger before utilizes.Data collecting on observational it utilizes to methodic observation, interview and `studi` is library.Meanwhile software development methods that is utilized is model Waterfall. Implementation of model Waterfall this was worded utilize `document`'s flowing charts, diagram context, `flow`'s data diagramdesignoutput` is input design databasedata dictionary,coded system,application menu design,and logic design programs(flowchart).this observational result make easy clerk in `mendata`(entry), erase, fix, searching sell data, acquisition `stok`'s checking doctor doctor.sell reporting and `stok` is doctor can quickly be gotten so makes easy firm in controls sell.Keywords :System informations, sale, distribution